Levamisole, as a viral vaccine adjuvant, induces robust host defense through the modulation of innate and adaptive immune responses - Kim, Gang Sik; Kwak, Dong Yun; Kim, Hyeong Won; Shin, Seokwon; Ko, Mi-Kyeong; Hwang, Seong Yun; Park, So Hui; Kim, Dong Hyeon; Park, Jong-Hyeon; Kim, Su-Mi; Lee, Min Ja (Frontiers in Microbiology, 2025)
IntroductionAn effective vaccination policy must be implemented to prevent foot-and-mouth disease (FMD). However, the currently used vaccines for FMD have several limitations, including induction of humoral rather than cellular immune responses.MethodsTo overcome these shortcomings, we assessed the efficacy of levamisole, a small-molecule immunomodulator, as an adjuvant for the FMD vaccine. We conducted in vitro studies using murine peritoneal exudate cells (PECs) and porcine peripheral blood mononuclear cells (PBMCs) and in vivo studies using mice (experimental animals) and pigs (target animals). We evaluated levamisole-mediated modulation of the innate and adaptive immune responses; early, mid-term, and long-term immune-inducing effects; modes of action; and host defense against viral infection.ResultsLevamisole treatment promoted IFNγ secretion in murine PECs and porcine PBMCs. Additionally, it induced robust and long-lasting immune responses by eliciting high antibody titers and high virus-neutralizing antibody titers. By activating downstream signaling pathways of various pattern-recognition receptors, levamisole stimulated the expression of multiple cytokines and costimulatory molecules. Owing to these immunostimulatory effects, levamisole elicited host defense against viral infections in pigs. Our findings demonstrate the potential of levamisole as an immunostimulatory agent.DiscussionThe results also indicate that levamisole, as an adjuvant for animal vaccines, can elicit robust innate and adaptive immune responses, thereby enhancing host defense against viral infections. This study provides a promising approach for the development of improved FMD vaccine strategies in the future.